A collaborative routing protocol for video streaming with fog computing in vehicular ad hoc networks. (March 2019) - Bezerra, Paulo; Melo, Adalberto; Douglas, Allan; Santos, Hugo; Rosário, Denis; Cerqueira, Eduardo
Vehicular ad hoc networks play an important role in the efficiency of road traffic by improving safety and acting as a facilitator of services for passengers, drivers, and public safety officers. Recent improvements in the routing protocols and topologies used in vehicular networks have contributed to improvements in scalability, reliability, and the quality of the information-sharing experience. Vehicles can cooperate with each other to stream videos of accidents or disasters and provide visual information of the monitored area with great precision. This article proposes a collaborative routing protocol for video streaming vehicular ad hoc networks using the service of fog storage to minimize the sharing of content. The routing table is based on an indicator that is generated by combining the speed, location, and recording angle parameters of each vehicle involved in vehicular collaboration to reduce the unnecessary exchange of video data in vehicle-to-vehicle communications. The results of the simulations show that the proposed model performs favorably when compared with other routing protocols with respect to the availability of end-to-end communication.